Anomalous diffusion modeling using ultracapacitors in domino ladder circuit. (February 2019) - Skovranek, Tomas; Macias, Michal; Sierociuk, Dominik; Malesza, Wiktor; Dzielinski, Andrzej; Podlubny, Igor; Pocsova, Jana; Petras, Ivo
Abstract: This article deals with the anomalous diffusion modeling using analog and mathematical models. To model the anomalous diffusion process the analog circuit is proposed, where for the first time instead of the classical capacitors in domino ladder structure, the ultracapacitors are used. On illustrative example we present a comparison of mathematical model and real electrical circuit measurement with a very good consistency.